(untitled) (Journal of Biomedical Investigation, 2007)
The study was designed to assess the effect of HIV infection on CD4’T cell count, IL-6 and IFN-y in HIV infected individuals. Forty-five HIV positive subjects (male 27, female 18), aged between 15-65 years were recruited for the study. 21 of this (male 10, female=11) were HIV symptomatic individuals, while the remaining 24 subjects (male=17, female=7), were HIV asymptomatic individuals; 22 HIV seronegative subjects served as control individuals. Blood samples collected from all the individuals that participated in the study were used for the determination of HIV status by immunochromatographic method, CD4’T cell count by Flow Cytometry, IFN-y and IL-6 by ELISA method. The result showed diminished CD4’T cells count and serum concentration of IFN-y in HIV symptomatic individuals (P<0,.05 in each case). Meanwhile, the serum IL-6 concentration was similar amongst the three groups (p>0.1): The drop in both the CD4’T cell count and serum concentration of IFN-y in the HIV symptomatic individuals suggests possible progression in impairment of certain immunologic responses during HIV infection.